2012
DOI: 10.1021/bi300150y
|View full text |Cite
|
Sign up to set email alerts
|

Structure of MMACHC Reveals an Arginine-Rich Pocket and a Domain-Swapped Dimer for Its B12 Processing Function

Abstract: Defects in the MMACHC gene represent the most common disorder of cobalamin (Cbl) metabolism, affecting synthesis of the enzyme cofactors adenosyl-Cbl and methyl-Cbl. The encoded MMACHC protein binds intracellular Cbl derivatives with different upper axial ligands and exhibits flavin mononucleotide (FMN)-dependent decyanase activity toward cyano-Cbl as well as glutathione (GSH)-dependent dealkylase activity toward alkyl-Cbls. We determined the structure of human MMACHC·adenosyl-Cbl complex, revealing a tailor-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(91 citation statements)
references
References 32 publications
3
83
0
5
Order By: Relevance
“…The flavin-and substrate-binding sites are located at the dimer interface in these proteins. In contrast, CblD and CblC do not form dimers in solution, and the dimerization interface seen in their crystal structures is distinct from that of other NFR family members in that it does not involve the long helix (28,42).…”
Section: ⌬N108mentioning
confidence: 83%
See 1 more Smart Citation
“…The flavin-and substrate-binding sites are located at the dimer interface in these proteins. In contrast, CblD and CblC do not form dimers in solution, and the dimerization interface seen in their crystal structures is distinct from that of other NFR family members in that it does not involve the long helix (28,42).…”
Section: ⌬N108mentioning
confidence: 83%
“…6, A and B). Solution of the crystal structure of CblC led to the recognition that it resembles some members in the NFR superfamily (28,42). CblC and CblD share an identical core of antiparallel ␤-sheets with similar structural elements in comparable arrangements framing the core.…”
Section: Cblc Is the Closest Structural Homolog Of Cbld-althoughmentioning
confidence: 99%
“…Studies with the bovine isoform of MMACHC revealed that the reduced form of glutathione stabilizes MMACHC, suggesting that intracellular redox control could play a role in the regulation of the protein ' s lifetime [ 41 -44 ]. Koutmos [ 3 ] and Froese [ 45 ] glutathione-binding pocket up above the β -axial ligand position [ 45 ]. Importantly, the arginine-rich pocket comprises residues Arg161, Arg206 and Arg230 ( recombinant mutant Arg206Gln was insoluble suggesting a structural role for this residue, and that mutants Arg161Gln and Arg230Gln abolished GSH binding and dealkylase activity, which is a strong indication that these amino acid residues are critical for GSH binding [ 45 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 94%
“…Koutmos [ 3 ] and Froese [ 45 ] glutathione-binding pocket up above the β -axial ligand position [ 45 ]. Importantly, the arginine-rich pocket comprises residues Arg161, Arg206 and Arg230 ( recombinant mutant Arg206Gln was insoluble suggesting a structural role for this residue, and that mutants Arg161Gln and Arg230Gln abolished GSH binding and dealkylase activity, which is a strong indication that these amino acid residues are critical for GSH binding [ 45 ]. The authors noted that FMN, and to a lesser extent Cbl, induces the dimerization of MMACHC, a previously unrecognized feature of the protein [ 45 ].…”
Section: Biophysical and Structural Characterization Of The B 12 -Promentioning
confidence: 99%
“…Furthermore, MMACHC has been proposed to interact with combined methylmalonic aciduria and homocystinuria cblD type (MMADHC), the downstream protein in the cobalamin pathway (Deme et al 2012;Plesa et al 2011). Recently the three-dimensional structure of human MMACHC was determined (Froese et al 2012;Koutmos et al 2011). This provides a structural framework to understand the effects of MMACHC mutations and gives new biochemical insight into the catalytic functions of MMACHC.…”
Section: Introductionmentioning
confidence: 99%